If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 + 3x + 6 = 58.3 Reorder the terms: 12 + 6 + 6x + 3x = 58.3 Combine like terms: 12 + 6 = 18 18 + 6x + 3x = 58.3 Combine like terms: 6x + 3x = 9x 18 + 9x = 58.3 Solving 18 + 9x = 58.3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 9x = 58.3 + -18 Combine like terms: 18 + -18 = 0 0 + 9x = 58.3 + -18 9x = 58.3 + -18 Combine like terms: 58.3 + -18 = 40.3 9x = 40.3 Divide each side by '9'. x = 4.477777778 Simplifying x = 4.477777778
| rtd=rt | | 11-(-6)= | | (4x-7y)-(x-3y)= | | 6x^2+66x+60=0 | | 25+4x^2-4x=3x^2-6x | | -32x^7-8x^6= | | 12x=x-2(16) | | x+.20x=34.80 | | -25+4(2x+5)=-16 | | 2x+3-7x+2=10 | | 3(n+7)=-6 | | X+x+.5x+.5x=360 | | 8t-11=5t-5 | | 15x^2-29x+120=0 | | -4(x+1)=5x+5 | | -4x^2-4x-8=0 | | 15x^2-29x+29=0 | | 4d-13+7=-24 | | 6v+28=2(v+6) | | 4x^2-4v-8=0 | | 0=-16t^2+10t+1 | | [-14+(-7)]+[-8+13]= | | 5x+9=140 | | 3x=2y^2 | | 4d-13=-24 | | 13=5-13+3 | | 36=8w+2.6-36 | | 7m=-19 | | 9v^2+23v+14=0 | | h=-16t^2+10t+1 | | 50h=60h | | -x-2y=7 |